2016
DOI: 10.1016/j.tibs.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Bioactive Compounds into Membranes: The UbiA Superfamily of Intramembrane Aromatic Prenyltransferases

Abstract: The UbiA superfamily of intramembrane prenyltransferases catalyzes a key biosynthetic step in the production of ubiquinones, menaquinones, plastoquinones, hemes, chlorophylls, vitamin E, and structural lipids. These lipophilic compounds serve as electron and proton carriers for cellular respiration and photosynthesis, as antioxidants to reduce cell damage, and as structural components of microbial cell walls and membranes. This article reviews the biological functions and enzymatic activities of representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 98 publications
0
109
0
Order By: Relevance
“…Most of the EboC protein length aligns to the UbiA family model in Pfam and vice versa , and no other additional conserved domain could be found in EboC proteins, indicating that they entirely correspond to UbiA homologues. UbiA, an enzyme (4-hydroxybenzoate polyprenyltransferase) involved in ubiquinone biosynthesis [67], is a prototype of a much broader group of proteins with a similar structure and biochemical function, recently denoted as the UbiA superfamily [50]. Members of this group are intramembrane proteins that catalyse attachment of (poly)prenyl chains or their derivatives to different substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the EboC protein length aligns to the UbiA family model in Pfam and vice versa , and no other additional conserved domain could be found in EboC proteins, indicating that they entirely correspond to UbiA homologues. UbiA, an enzyme (4-hydroxybenzoate polyprenyltransferase) involved in ubiquinone biosynthesis [67], is a prototype of a much broader group of proteins with a similar structure and biochemical function, recently denoted as the UbiA superfamily [50]. Members of this group are intramembrane proteins that catalyse attachment of (poly)prenyl chains or their derivatives to different substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we applied a sequence clustering method recently used for mapping the sequence space of the UbiA superfamily, yet without EboC proteins (see fig. 1 in [50]). Our analysis revealed that EboC proteins constitute a distinct sequence cluster within the UbiA superfamily (figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules play key roles in electron and proton transport and respiration, photosynthesis, lipid metabolism, cell signaling, and cell wall formation [59]. They can also act as antioxidants and cofactors [61].…”
Section: Structural Basis Of Interfacial Lipid Modificationmentioning
confidence: 99%
“…For example, UBIAD1 transfers an isoprenyl chain from geranylgeranyl pyrophosphate to menadione phylloquinone yielding menaquinone-4 (the major storage form of vitamin K) important in mitochondria, while in the Golgi, it participates in the synthesis of ubiquinone UQ 10 by a similar mechanism. Exceptions to this observed substrate promiscuity exist within the family, such as PHB geranyltransferase from Lithospermum erythrorhizon, which can only utilize geranylpyrophosphate (GPP) as a prenyl donor [59]. The promiscuity or fidelity of enzymes of the same family for lipidic substrates presents an intriguing problem from a structural perspective.…”
Section: Structural Basis Of Interfacial Lipid Modificationmentioning
confidence: 99%